Fabrication of extreme ultraviolet lithography pellicle with nanometer-thick graphite film by sublimation of camphor supporting layer. (23rd August 2021) - Nam, Ki-Bong; Yeo, Jin-Ho; Hu, Qicheng; Kim, Mun Ja; Oh, Byungdu; Yoo, Ji-Beom
Abstract: An extreme ultraviolet (EUV) pellicle consists of freestanding thin films on a frame; these films are tens of nanometers in thickness and can include Si, SiN X, or graphite. Nanometer-thick graphite films (NGFs), synthesized via chemical vapor deposition on a metal catalyst, are used as a pellicle material. The most common method to transfer NGFs onto a substrate or a frame is to use polymethyl methacrylate (PMMA) as a supporting layer. However, this PMMA-mediated technique involves several disadvantages in term of manufacturing NGF EUV pellicles. When removing the PMMA using acetone or O2 plasma, defects or deflections can occur in the NGFs. Furthermore, PMMA residues are generally present on large-area NGFs. In this study, a transfer method using camphor instead of PMMA as the supporting layer was developed to overcome these problems. After the camphor/NGF was formed on the frame, camphor was removed via sublimation in an atmosphere of ethanol vapor. This study investigated the deposition and sublimation of camphor, and confirmed that no residue was present and no deflection or defects were observed in the NGFs. Thus, a large-area NGF pellicle was successfully fabricated using the camphor transfer process.